USE OF INNOVATIVE EDUCATIONAL METHODS AND TECHNOLOGIES IN THE TEACHING OF SPECIALISTS IN THE PROFESSIONAL EDUCATION SYSTEM - Ruzimurotova Yulduz Shomurotovna; Usmonova Dilfuza Mukhiddinjonovna (PEDAGOGS, 2024)
The article examines the problems related to the innovative educational activities of professional educational institutions, and some innovative methods of teaching in educational institutions that have proven themselves in world practice are studied. The changing role of the teacher is observed in the process of transition from passive to active and interactive educational models. Special attention is paid to pedagogical laws of educational innovation.